Agricultural press agency - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A new agricultural information agency, SYFIA (Systeme Francophone d'lnformation Agricole) is linking 30 francophone countries from the developing world. It aims to maximize the effectiveness of their work done in the fields of development and...